The readiness of Fiqh teachers in applying the deep learning pedagogical approach in the independent curriculum: a qualitative case study at Madrasah Tsanawiyah Muslimat Nahdhatul Ulama Indonesia - Alawiyah, Rabbiatul; Hartati, Zainap; Sapuadi, Sapuadi (UIR Press, 2026)
The implementation of deep learning approaches within Indonesia’s Independent Curriculum requires teachers to demonstrate both conceptual understanding and pedagogical readiness. However, limited empirical evidence exists regarding teachers’ readiness to operationalize deep learning principles in Islamic secondary education. This study aims to analyze the readiness of Fiqh teachers in implementing a deep learning approach within the Independent Curriculum at MTs Muslimat NU Palangka Raya. The research employed a qualitative descriptive design involving Fiqh teachers as the primary participants. Data were collected through in-depth interviews, classroom observations, and analysis of instructional documents, including teaching modules and lesson plans. Data validity was ensured through triangulation of sources and techniques. The findings indicate that teachers possess an adequate conceptual understanding of deep learning and attempt to implement it through discussion-based learning, problem-solving strategies, and reflective learning practices. However, the systematic integration of deep learning principles into instructional planning—particularly in the development of structured teaching modules—remains limited. Consequently, teachers’ readiness can be categorized as moderate. This study highlights the need for targeted professional development and continuous mentoring to strengthen teachers’ pedagogical competence. The originality of this study lies in its focus on teacher readiness for deep learning implementation within the madrasah context under the Independent Curriculum reform.